Case report: Diagnosis and treatment of DGAT1 deficiency-induced congenital diarrhea in two cases and literature review - Li, Jian; Sun, Mei; Guo, Jing; Xu, Lingfen (Frontiers in Pediatrics, 2023)
Introduction Congenital diarrhea is a rare inherited intestinal disease characterized by persistent and severe diarrhea and malabsorption in the first few weeks after birth, which can be life-threatening. Some congenital diarrheal diseases are associated with mutations in the diacylglycerol acyltransferase 1 (DGAT1) gene. Case descriptions This study delineated 2 cases of diarrhea and growth retardation, subsequently confirmed as congenital diarrhea via genetic testing, revealing that the etiology involved compound heterozygous mutations in the DGAT1 gene. Diagnostic assessments High-MCT milk powder did not obtain an ideal outcome, whereas low-fat diets improved the symptoms of diarrhea and increased the body weigths. Disscussion The two cases facilitated our understanding of the clinical features of, and treatments for, patients harboring a DGAT1 mutation and enriched the existing DGAT1 mutation database.